Making IT Project De-Escalation Happen: An Exploration into Key Roles - Mähring, Magnus; Keil, Mark; Mathiassen, Lars; Pries-Heje, Jan (Journal of the Association for Information Systems, 2008)
Given the persistent and costly problem of escalating IT projects, it is important to understand how projects can be de-escalated successfully, resulting in project turnaround if possible, or termination if necessary. Recent work suggests that the instantiation of specific roles may be central in bringing about de-escalation. However, few such roles have been identified to date and there has been no systematic study of key roles. In this paper, we therefore explore roles in IT project de-escalation using a single-case approach. Results suggest that de-escalation not only depends on the existence of particular roles, but also on role interaction. We identify seven roles that are of substantial importance in shaping whether and how de-escalation is carried out: messenger, exit sponsor, exit champion, exit blocker, exit catalyst, legitimizer, and scapegoat. Furthermore, we offer a set of propositions that capture key role interactions during de-escalation. Implications for research and practice are discussed. [PUBLICATION ABSTRACT]